Emergence of azole-resistant invasive aspergillosis in HSCT recipients in Germany. (27th January 2015) - Steinmann, J.; Hamprecht, A.; Vehreschild, M. J. G. T.; Cornely, O. A.; Buchheidt, D.; Spiess, B.; Koldehoff, M.; Buer, J.; Meis, J. F.; Rath, P.-M.
Abstract: Objectives: Aspergillus fumigatus is the most common agent of invasive aspergillosis (IA). In recent years, resistance to triazoles, the mainstay of IA therapy, has emerged in different countries worldwide. IA caused by azole-resistant A. fumigatus (ARAF) shows an exceedingly high mortality. In this study, IA due to ARAF isolates in HSCT recipients in Germany was investigated. Methods: The epidemiology of azole resistance in IA was analysed in two German haematology departments. Between 2012 and 2013, 762 patients received HSCT in Essen ( n = 388) and Cologne ( n = 374). Susceptibility testing of A. fumigatus isolates was performed by Etest, followed by EUCAST broth microdilution testing if elevated MICs were recorded. In all ARAF isolates the cyp51A gene was sequenced and the genotype was determined by microsatellite typing using nine short tandem repeats. Results: In total, A. fumigatus was recovered from 27 HSCT recipients. Eight patients had azole-resistant IA after HSCT, and seven of the cases were fatal (88%). All except one patient received antifungal prophylaxis (in five cases triazoles). TR34 /L98H was the most common mutation ( n = 5), followed by TR46 /Y121F/T289A ( n = 2). In one resistant isolate no cyp51A mutation was detected. Genotyping revealed genetic diversity within the German ARAF isolates and no clustering with resistant isolates from the Netherlands, India and France. Conclusions: This report highlights the emergence of azole-resistant IA with TR34 /L98H and TR46 /Y121F/T289A mutations in HSCT patients in Germany and underscores the need for systematic antifungal susceptibility testing of A. fumigatus .